2022
DOI: 10.3389/fpubh.2022.835914
|View full text |Cite
|
Sign up to set email alerts
|

High expression of protein tyrosine phosphatase receptor S (PTPRS) is an independent prognostic marker for cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is an aggressive tumor of the bile duct with a high rate of mortality. Lymph node metastasis is an important factor facilitating the progression of CCA. A reliable biomarker for diagnosis, progression status, or prognosis of CCA is still lacking. To identify a novel and reliable biomarker for diagnosis/prognosis of CCA, liquid chromatography-mass spectrometry and tandem mass spectrometry (LC-MS/MS) in combination with bioinformatics analysis were applied for the representative serum sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(56 reference statements)
1
0
0
Order By: Relevance
“…ALP has anti-inflammatory and anti-tumor activities, and ALP has been shown to inhibit tumor progression and the continued spread of tumor tissue. [12] In this study, univariate analysis confirmed that ALP has prognostic significance for the OS and PFS of ICC. Moreover, retrospective analysis confirmed that AAPR may be of potential prognostic value for patients undergoing CCA surgery.…”
Section: Discussionsupporting
confidence: 72%
“…ALP has anti-inflammatory and anti-tumor activities, and ALP has been shown to inhibit tumor progression and the continued spread of tumor tissue. [12] In this study, univariate analysis confirmed that ALP has prognostic significance for the OS and PFS of ICC. Moreover, retrospective analysis confirmed that AAPR may be of potential prognostic value for patients undergoing CCA surgery.…”
Section: Discussionsupporting
confidence: 72%